Differentiation Learning Models in Mathematics: A Review of Literature - Siregar, Pariang Sonang; Nazurty, Nazurty; Sofyan, Hendra; Rosmiati, Rosmiati (PPSDP International Journal of Education, 2023)
Differentiated learning has become known in Indonesia since the existence of a “Guru Penggerak” program which was first held in 2020. Differentiated learning is a teaching and learning process that allows students to study subject matter based on their talents, preferences, and individual requirements. Differentiated learning can support the development of learning competencies, one of which is learning mathematics. A literature review is the research approach used in this study. The publications utilized in this study were published during the previous ten years, from 2013 to 2023. Based on the search results using Google Scholar, 34 articles were found that were appropriate and related to this research. The results of the study found that the application of differentiated learning was able to improve learning outcomes, and understanding of the concept of creativity, achievement, interest, and motivation to learn.